Age-related variability in pediatric scalp thickness: Implications for auditory prostheses. (March 2020) - Sharma, Sunil D.; Park, Edward; Purcell, Patricia L.; Gordon, Karen A.; Papsin, Blake C.; Cushing, Sharon L.
Abstract: Objectives: Minimizing soft tissue reduction during the placement of percutaneous implants has been encouraged to improve cosmesis and perhaps decrease soft tissue complications. However, the fidelity of sound transmission and retention of transcutaneous magnet devices relates to the intervening soft tissue thickness. The objective of this study was to examine age-related variability in scalp thickness in patients receiving either percutaneously implanted or transcutaneous magnet-retained auditory prostheses. Methods: Children undergoing percutaneous implant retained prostheses or cochlear implantation underwent two scalp thickness measurements: 1) a superior measurement at the conventional marked site for cochlear implant receiver stimulator and 2) an inferior measurement 1.5 cm below the superior measurement representing the conventional marked site for cochlear implant fantail. Linear regression was used for statistical analysis. Results: Eighty-five children (median age 6 years; range 9 months–17 years) were examined. Scalp thickness at the two sites ranged from 1 to 10 mm (superior mean = 4.1 mm; inferior mean = 4.3 mm). A strong correlation was observed between age and scalp thickness at the superior (R = 0.62, p < 0.01 ) measurement, while a moderate correlation was observed at the inferior (R = 0.45, p < 0.01 ) sites. Children younger than 7 years displayed little variability in scalp thickness, and no correlation between age and scalp thickness (R = 0.002, p  =  0.74 ). Conclusion: In older children, scalp thickness varies significantly with age. However, children younger than 7 years consistently have scalp thicknesses of 3–4 mm. Lack of variability in scalp thickness in children younger than 7 years argues against the use of an age-adjusted approach to soft tissue management in this age group.